Backscatter properties of two-layer phantoms using a high-frequency ultrasound annular array. (1st July 2022) - Saito, Wakana; Omura, Masaaki; Ketterling, Jeffrey A.; Hirata, Shinnosuke; Yoshida, Kenji; Yamaguchi, Tadashi
Abstract: In a previous study, an annular-array transducer was employed to characterize homogeneous scattering phantoms and excised rat livers using backscatter envelope statistics and frequency domain analysis. A sound field correction method was also applied to take into account the average attenuation of the entire scattering medium. Here, we further generalized the evaluation of backscatter coefficient (BSC) using the annular array in order to study skin tissues with a complicated structure. In layered phantoms composed of two types of media with different scattering characteristics, the BSC was evaluated by the usual attenuation correction method, which revealed an expected large difference from the predicted BSC. In order to improve the BSC estimate, a correction method that applied the attenuation of each layer as a reference combined with a method that corrects based on the attenuation of the analysis position were applied. It was found that the method using the average attenuation of each layer is the most effective. This correction method is well adapted to the extended depth of field provided by an annular array.